Developing a compensation framework for land acquisition affecting Orang Asli native lands / Anuar Alias - Anuar, Alias (2009)
This research explores the issues of land rights and land acquisition compensation related to the Orang Asli in Peninsular Malaysia. Acquisition of Orang Asli native lands is inevitable as land is scarce to meet the national growth agenda and socio-economic developments. As an independent country, Malaysia provides constitutional guarantees, and customary land tenure is recognised and respected. Unfortunately, since land rights of Orang AsIi native land are not being clearly defined in Malaysian legal system, payment of compensation to acquisition of the land is unstructured, and disparity exists among the different states. lt is therefore pertinent to propose a uniform compensation framework for the acquisition of Orang AsIi native lands. The research adopts various approaches of study and triangulates the findings. The case study and quantitative survey methods are the main strategies for data collection, reinforced by the qualitative survey method using the Delphi Method in which consultation was sought from the experts on land acquisition compensation of Orang asli lands to enhance the validity of the research findings. This research revealed that laws of Malaysia are lacking with regard to the protection of Orang asli lands and rights to fair and just compensation. This research concludes that the posotion of Orang Asli land rights has not much improved. Due to this unresolved land rights issue, the present structure of compensation as spelt out under the sections 11 and 12 of the Aboriginal Peoples Act 1954 is perceived as inadequate. At present, in the absence of proper guidelines and regulations, the determination of compensation is solely based on the discretion of the various authorities. Some authorities apply the rules rigidly, while others are too generous. Additionally, this research proposes a compensation framework for land acquisition of Orang Asli native lands, which should possess two categories of compensation - monetary and non-monetary components. Finally, the research argues that proposed compensation framework is 'implementable and workable'. However, the degree of success in its implementation is subject to how far the Orang Asli land rights are resolved.